2012
DOI: 10.1007/s00210-012-0774-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with enalapril on hepatotoxicity induced by acetaminophen in mice

Abstract: There is a current need for new therapeutic options for acetaminophen (APAP)-induced hepatotoxicity. Herein, we assessed the effects of prophylactic and therapeutic treatment with the angiotensin-converting enzyme (ACE) inhibitor, enalapril, on APAP-caused hepatotoxicity. Male and female C57BL/6 J mice were used, and hepatotoxicity was induced by a single application of APAP (400 mg/kg, i.p.). Macroscopic and histological liver alterations, serum alanine transaminase (ALT) and aspartate transaminase (AST) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Liver samples were homogenized in saline and centrifuged at 3500g for 10 min for analysis of endogenous antioxidant status. CAT activity and GSH levels were determined according to the methodology described previously [29].…”
Section: Euthanasia and Biochemical Analysesmentioning
confidence: 99%
“…Liver samples were homogenized in saline and centrifuged at 3500g for 10 min for analysis of endogenous antioxidant status. CAT activity and GSH levels were determined according to the methodology described previously [29].…”
Section: Euthanasia and Biochemical Analysesmentioning
confidence: 99%
“…Many of these studies have shown that pretreatment or simultaneous treatment with diverse agents can provide protection against APAP hepatotoxicity. 19 , 20 Antioxidant agents have therapeutic potential in drug-induced toxicity. 21 NAC is used as present treatment for APAP toxicity, by replacing cellular GSH to prevent of cell damage by NAPQI.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, paracetamol poisoning was shown to increase ALT and AST activities in rabbits (43). Another study on the effects of ACE inhibitor enalapril on paracetamol-induced liver damage has found significantly reduced ALT and AST activities in mice treated with enalapril (44). The present study investigated the effects of another ACE inhibitor, omapatrilat, on ALT and AST activities.…”
Section: Discussionmentioning
confidence: 81%